Labor participation and subjective well-being of older adult: A systematic literature review - Xia, Li; Noradilah, Md Nordin (Creative Publishing House, 2024)
The consequence of the rapid aging population has received widespread attention globally. Recently, much attention has been given to the active aging population that exists in the elderly population who are currently working or employed. Therefore, this systematic literature review (SLR) investigates the empirical evidence on the association of older adults' labor participation and subjective well-being. Specifically, two main objectives of this study i.e., examine relationship between labor participation and subjective well-being, and other factors affecting older adults' subjective well-being. We used the PRISMA systematic literature review protocol and searched from two databases (i.e., Scopus and Web of Science) in March 2024. Fourteen studies were included in this SLR. Five studies assessed the effect of personal attributes such gender, income, media use, and marital status on older adults' subjective well-being and eleven articles assessed the increase of labor participation/social participation on subjective well-being of older adults. Two of the articles simultaneously assessed the impact of personal attributes and labor participation/social participation on subjective well-being. The reported findings were classified into personal attributes, labor participation, and subjective well-being. The results of the study show that most researchers believe that older adults' labor participation/social participation and personal attributes are highly correlated with older adults' subjective well-being.